2016
DOI: 10.1073/pnas.1519368113
|View full text |Cite
|
Sign up to set email alerts
|

Programmable RNA-binding protein composed of repeats of a single modular unit

Abstract: The ability to monitor and perturb RNAs in living cells would benefit greatly from a modular protein architecture that targets unmodified RNA sequences in a programmable way. We report that the RNA-binding protein PumHD (Pumilio homology domain), which has been widely used in native and modified form for targeting RNA, can be engineered to yield a set of four canonical protein modules, each of which targets one RNA base. These modules (which we call Pumby, for Pumilio-based assembly) can be concatenated in cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…Adamala et al. concatenated single PUF repeats in chain to target desired RNA sequences and showed that repeat 6 could be a template for the canonical modules . Therefore, repeat 6 might have high structural tolerance for the neighboring repeat, which leads to preferable binding activity of insertion‐type 16‐repeat PUFs.…”
Section: Resultsmentioning
confidence: 99%
“…Adamala et al. concatenated single PUF repeats in chain to target desired RNA sequences and showed that repeat 6 could be a template for the canonical modules . Therefore, repeat 6 might have high structural tolerance for the neighboring repeat, which leads to preferable binding activity of insertion‐type 16‐repeat PUFs.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA specificity of the PUF domain has been well decoded (44)(45)(46). Based on the properties of the PUF proteins, the programmable RNA binding by the engineered PUF protein has been realized (47)(48)(49)(50). Moreover, the PUF domains fusing with a general RNA cleavage domain have been generated to the artificial site-specific RNA endonucleases that specifically recognize and cleave RNA targets (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…So far, we have only demonstrated the activity of PAM2 motifs by tethered function analysis. However, PAM2 peptides also may be combined with sequence-specific RNA-binding molecules, such as Pumilio homology domains5051, CRISPR-Cas95253 or antisense oligonucleotides54 to suppress NMD independent of tethering. Applied in combination with read-through drugs, PAM2 peptides may also enable to restore the expression of nonsense-mutated genes.…”
Section: Discussionmentioning
confidence: 99%